2019
DOI: 10.1016/j.bpj.2018.11.3090
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for Release Factor Activation during Translation Termination Revealed by Time-Resolved Cryogenic Electron Microscopy

Abstract: 70S E-coli ribosomes bound to a trans-translation inhibitor. Using cryogenic electron microscopy, we have resolved the binding site of the drug and have observed novel conformational changes in the ribosomal protein L27. We will discuss how these observations help explain the mechanism by which drugs can target trans-translation without affecting normal translation. These studies will further help to improve the design of antibiotics that target rescue pathways in bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The major advances reported here as well as by others 21,26 prompt further meaningful improvements to trEM. Currently, the amount of sample consumed per experiment is large in comparison to other sample preparation approaches 33,60,61 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The major advances reported here as well as by others 21,26 prompt further meaningful improvements to trEM. Currently, the amount of sample consumed per experiment is large in comparison to other sample preparation approaches 33,60,61 .…”
Section: Discussionsupporting
confidence: 61%
“…To overcome these limitations and develop a general time-resolved sample preparation method for cryo-EM (trEM) requires building a miniaturized mixer and bioreactor able to rapidly initiate and synchronize biochemical reactions, followed by spreading the incubated sample onto a cryo-EM grid without the need for manual operation or blotting, collectively faster than the lifetime of the structures of interest 19 . Previous work has shown that combining reactants in microfluidic devices followed by rapid application of sample by gasassisted spraying is in principle possible [20][21][22][23][24][25] , and has yielded fascinating new insights into biology 26 . However, substantial technical challenges remain unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…Our termination structures allow us to reconstruct a dynamic pathway for termination ( Figure 4 and Movie 1) and reconcile biophysical and biochemical findings (Adio et al, 2018;Casy et al, 2018;Prabhakar et al, 2017;Sternberg et al, 2009). Recent structural studies revealed compact RF conformations on non-rotated 70S ribosomes (Fu et al, 2018;Svidritskiy and Korostelev, 2018a) that suggest how RFs open at early stages of codon recognition (He and Green, 2010;Hetrick et al, 2009;Trappl and Joseph, 2016). The short-lived transition from compact to open conformation(s) lasts tens of microseconds (Fu et al, 2018), and compact RF2 conformations were not captured in our sample.…”
Section: Mechanism Of Translation Termination By Rf2mentioning
confidence: 61%
“…Recent structural studies revealed compact RF conformations on non-rotated 70S ribosomes (Fu et al, 2018;Svidritskiy and Korostelev, 2018a) that suggest how RFs open at early stages of codon recognition (He and Green, 2010;Hetrick et al, 2009;Trappl and Joseph, 2016). The short-lived transition from compact to open conformation(s) lasts tens of microseconds (Fu et al, 2018), and compact RF2 conformations were not captured in our sample. Compact RF2 was also visualized by cryo-EM on the 70S ribosome in the presence of truncated mRNA and alternative rescue factor A (ArfA) James et al, 2016), suggesting a conserved pathway for initial binding of RFs to non-rotated ribosomes.…”
Section: Mechanism Of Translation Termination By Rf2mentioning
confidence: 75%
“…With the recent developments in cryoEM hardware and software, developing a reliable TrEM setup is becoming a reality. In this work we report an advanced system which can produce cryoEM grids with a minimum time delay between mixing and freezing of 10 ms, faster than the previously reported fastest speed of 24ms 21 . Through three model systems we have shown the capability of producing high quality EM data at a resolution sufficient for resolving side chain density.…”
Section: Discussionmentioning
confidence: 88%